PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN PADA UPTD PUSKESMAS KABANJAHE KECAMATAN KABANJAHE KABUPATEN KARO - Tarigan, Rendy Franata; Saragih, Nawary (LPPM Universitas Katolik Santo Thomas Medan, 2022)
This study aims to determine the effect of service quality (tangible, empathy, reliability, responsiveness, and assurance) on patient satisfaction at the Regional Technical Implementation Unit of the Community Health Center (UPTD Puskesmas) Kabanjahe, Kabanjahe District, Karo Regency. Data obtained directly from respondents (patients). The number of samples with maximum error (error) obtained 96 people. The analysis technique used in this research is validity and reliability test, multiple linear regression, and hypothesis testing. The results of the study with the equation Y=2,074+0,087B+0,284E-0,007KH+0,116KT+0,400J+ e. This means that the quality of service (tangible, empathy, reliability, responsiveness and assurance) reflects that there is still a problem of patient dissatisfaction with the quality of services provided by the Health Center. The results of the F test, that the quality of service (tangible, empathy, reliability, responsiveness and assurance) simultaneously has a positive and significant effect on patient satisfaction. This can be seen from the significant value of 0.000 < 0.05 . The results of the t test, tangibles and responsiveness partially have a positive but not significant effect, and reliability have a negative and insignificant effect on patient satisfaction. While the results of the t test, empathy and assurance partially have a positive and significant effect on patient satisfaction. The value of the determinant coefficient (R Square) is 0.601, meaning that patient satisfaction can be explained by the quality of service (tangible, empathy, reliability, responsiveness, and assurance) of 60.1%, while another 39.9% is explained by other variables that are not explained. in this research, such as security, location, environment etc. Based on the results of the study that by looking at the results of the t test, tangibles and responsiveness partially have a positive but not significant effect, and reliability have a negative and insignificant effect on patient satisfaction. So it is suggested that the management of the Health Center needs improvement (officers who can provide health services reflect a high commitment to the principles of health services at the Kabanjahe Health Center in Karo Regency. The equipment provided is incomplete. The service is in accordance with the promises offered. The ability of the medical team to use assistive devices in the service process ) to increase patient satisfaction. Then by looking at the magnitude of other factors (39.9%) of patient dissatisfaction with the quality of service (tangible, empathy, reliability, responsiveness, and assurance), the management of this health center still needs to make improvements in many ways for service satisfaction to the community.